1997
DOI: 10.1177/096032719701600303
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive toxicity and toxicokinetics of lindane in the male offspring of rats exposed during lactation

Abstract: 1 Reproductive toxicity and toxicokinetics of lindane during lactation were studied. For the reproductive toxicity study the dams were treated with a single dose of 6 mg/kg on day 9 or 14 of lactation, or with 1 mg/kg on days 9 to 14 of lactation. The male offspring were investigated at puberty and adulthood. For the toxicokinetic study, two groups of dams were treated with 6 mg/kg on day 9 or 14 of lactation. The concentration of lindane was measured in maternal plasma and milk, as well as in male of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 31 publications
2
31
1
Order By: Relevance
“…Testicular damage, reduced sperm counts (Dalsenter et al, 1996), prolongation of the estrous cycle, and delayed vaginal opening (Uphouse and Williams, 1989;Chadwick et al, 1988;Cooper et al, 1989) have also been reported in rats. In addition, there have been descriptions of testicular damage and reduced sperm counts in F1 male rats after administration to lactating dams (Dalsenter et al, 1997). The present two-generation reproduction toxicity study in rats adding extra endpoints to detect endocrine disrupting activity, including AGD, nipple development, sexual maturation, estrous cycle, spermatogenesis, sex organ weights, and blood hormone concentrations, was performed to assess comparative utility.…”
Section: Introductionmentioning
confidence: 99%
“…Testicular damage, reduced sperm counts (Dalsenter et al, 1996), prolongation of the estrous cycle, and delayed vaginal opening (Uphouse and Williams, 1989;Chadwick et al, 1988;Cooper et al, 1989) have also been reported in rats. In addition, there have been descriptions of testicular damage and reduced sperm counts in F1 male rats after administration to lactating dams (Dalsenter et al, 1997). The present two-generation reproduction toxicity study in rats adding extra endpoints to detect endocrine disrupting activity, including AGD, nipple development, sexual maturation, estrous cycle, spermatogenesis, sex organ weights, and blood hormone concentrations, was performed to assess comparative utility.…”
Section: Introductionmentioning
confidence: 99%
“…Lindane had a toxic effect on the reproductive system at the dose of 5 mg/kg/bw/day and higher doses in rodents (Dalsenter et al 1997;FAO/WHO 2002). In previous studies, lindane was used at the doses of 1-30 mg/kg/bw in 30-90-day-old male rats and degenerative changes were reported (Chowdhury et al 1987;Srinivasan et al 1988;Dalsenter et al 1996;Dalsenter et al 1997;Walsh and Stocco 2000;Samanta and Chainy 2002).…”
mentioning
confidence: 99%
“…It causes damage to the male reproduction tract either acting directly on the testes or indirectly through endocrine regulation of the testes (Dalsenter et al 1996;Dalsenter et al 1997).…”
mentioning
confidence: 99%
“…Livers and one of the two testes were fixed in a 10% neutral buffered formalin solution for routine histological processing and light microscopic evaluation of sections stained with hematoxylin-eosin. The number of spermatozoa in the remaining testis and cauda epididymis was counted as described elsewhere (15) …”
Section: Evaluation Of the Animalsmentioning
confidence: 99%